2019
DOI: 10.1111/1365-2745.13310
|View full text |Cite
|
Sign up to set email alerts
|

Fungal connections between plants and biocrusts facilitate plants but have little effect on biocrusts

Abstract: 1. Species interactions may couple the resource dynamics of different primary producers and may enhance productivity by reducing loss from the system. In low-resource systems, this biotic control may be especially important for maintaining productivity. In drylands, the activities of vascular plants and biological soil crusts can be decoupled in space because biocrusts grow on the soil surface but plant roots are underground, and decoupled in time due to biocrusts activating with smaller precipitation events t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 71 publications
(83 reference statements)
4
37
0
Order By: Relevance
“…Similar to the lack of translocation from plants to biocrusts observed in our study, Dettweiler‐Robinson et al. (2020) found that some North American grasses benefitted from a fungal loop connection to cyanobacterial biocrusts, while this relationship had neutral to negative effects on the biocrust communities depending on precipitation regime. Considering that C movement from grasses to cyanobacterial biocrusts has been shown to occur (Green et al., 2008), our results suggest that the drivers for or mechanisms involving C exchange in previous studies were not present in this shrubland system or under these moisture conditions.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the lack of translocation from plants to biocrusts observed in our study, Dettweiler‐Robinson et al. (2020) found that some North American grasses benefitted from a fungal loop connection to cyanobacterial biocrusts, while this relationship had neutral to negative effects on the biocrust communities depending on precipitation regime. Considering that C movement from grasses to cyanobacterial biocrusts has been shown to occur (Green et al., 2008), our results suggest that the drivers for or mechanisms involving C exchange in previous studies were not present in this shrubland system or under these moisture conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Given that our study limited precipitation to 2.5 mm to simulate a common rain event for the season, it is likely that this rainfall event was not suitable to fully reinstate metabolic activity in the L. tridentata found in our study plots and therefore led to the lack of bidirectional nutrient exchange in this system. Similar to the lack of translocation from plants to biocrusts observed in our study, Dettweiler-Robinson et al (2020) found that some North American grasses benefitted from a fungal loop connection to cyanobacterial biocrusts, while this relationship had neutral to negative effects on the biocrust communities depending on precipitation regime. Considering that C movement from grasses to cyanobacterial biocrusts has been shown to occur (Green et al, 2008), our results suggest that the drivers for or mechanisms involving C exchange in previous studies were not present in this shrubland system or under these moisture conditions.…”
Section: Translocation Of Carbonsupporting
confidence: 88%
See 3 more Smart Citations